2021
DOI: 10.2174/1871526520666201116103625
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibiotic Resistance Genes Among Multiple Drug Resistant Pseudomonas Aeruginosa Isolated from Clinical Sources in Selected Health Institutions in Kwara State

Abstract: Background: Pseudomonas aeruginosa (P. aeruginosa) is a frequent nosocomial pathogen that causes severe diseases in many clinical and community settings. Strains of P. aeruginosa are associated with increased morbidity, mortality and healthcare costs. The rapid emergence of antimicrobial resistance among these strains is a public health crisis. Moreover, there is paucity of data on characterization of P. aeruginosa isolates from human clinical samples in Kwara State. Objectives: The objectives are to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…e antibiotic susceptibility testing also noted high resistance to antibiotics such as gentamicin (75.2%) and ceftriaxone (50.4%). As in the current study, numerous other researchers have already reported a decreased susceptibility of P. aeruginosa to the commonly used antibiotics (Dehbashi et al [10] and Adekunle et al [21]). Among P. aeruginosa, 49.5% of isolates were MDR, 19.2% were XDR, and 9.1% were PDR.…”
Section: Discussionsupporting
confidence: 79%
“…e antibiotic susceptibility testing also noted high resistance to antibiotics such as gentamicin (75.2%) and ceftriaxone (50.4%). As in the current study, numerous other researchers have already reported a decreased susceptibility of P. aeruginosa to the commonly used antibiotics (Dehbashi et al [10] and Adekunle et al [21]). Among P. aeruginosa, 49.5% of isolates were MDR, 19.2% were XDR, and 9.1% were PDR.…”
Section: Discussionsupporting
confidence: 79%
“…The ESBL-producing isolates of P. aeruginosa strains are linked to higher rates of morbidity, mortality, and medical expenses. A public health emergency is the quick spread of antibiotic resistance among these strains (Adekunle et al,2021).…”
Section: Pcr Assay Resultsmentioning
confidence: 99%
“…Most of the articles report bacteria with resistance to antibiotics based on conventional methods (as disk diffusion method, Double disc synergy test, dilution methods, Epsilometer test), especially in countries of Africa (2,11,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), Asia and Latin America (1, 6, 61-66). Phenotypic detection of antibiotic resistance by Disk Diffusion Method was reported in 60.5% of the total studies, followed by the Vitek 2 system (18.4%).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Isolates with Tn2006 has been detected in predominantly in Iran (113), while Tn2008, and Tn2009 in China (90,106). Also, high frequency of MDR pathogens harboring class 1 and 2 integrons have been detected in K. pneumoniae (9,14), A. baumannii (10,65,57,77,90,113), P. aeruginosa (18,94,101), and E. coli (38,64,110).…”
Section: Distribution Of Antibiotic Resistance Genes (Arg)mentioning
confidence: 99%